Information Economy: the Formation of Special-Purpose Categoriсal Framework - Semenyuk, E.P.; Kotlyarevsky, Ya.V.; Kniaziev, S.I.; Melnikov, O.V. (Science and Innovation, 2024)
The system of modern science categories as a whole has more or less clearly defined structure. The top-level general scientific and philosophical categories are supported by the regional ones, with a large set of special-purpose scientific categories being at the bottom of pyramid. Thus, it is appropriate to separate the main categories of information economy and to structure its relevant characteristics. At the same time, the authors have made an attempt to find clear definition of general features of special-purpose scientific categories as distinctive class of cognitive-methodological forms. Given the importance of social functions of information economy and prospects for its development the authors have contributed to study its features, peculiarities of object, subject, means, and branching of its conceptual and categorical framework.